Atherosclerosis and trimethylamine-N-oxide — the gut microbiota potential - I. N. Grigorieva (Российский кардиологический журнал)
Gut dysbiosis contribute to the development of atherosclerosis. Firmicutes contain a trimethylamine-producing gene cluster. The aim was to analyze potential role of trimethylamine-N-oxide (TMAO), gut microbiota metabolite, in the pathogenesis of atherosclerosis and novel therapeutic approaches to reduce TMAO. Some researchers consider TMAO not a mediator but a marker of cardiovascular disease because they have not confirmed associations between elevated TMAO levels, dyslipidemia, C-reactive protein, endotoxin, and cardiovascular mortality. But most studies recognize TMAO as an independent risk factor for serious cardiovascular events. TMAO inhibits reverse cholesterol transport, enhances foam cell formation and platelet hyperreactivity. The adverse effects of TMAO were positively correlated with gut enterotype III. Therapeutic effects on TMAO in atherosclerosis (probiotics, polyphenols, including resveratrol, berberine, trimethylamine lyase inhibitors, phospholipase D inhibitors, reducing the Firmicutes/Bacteroidetes ratio, enriching potentially beneficial genera Akkermansia, Lactobacillus, Bacteroides, Roseburia) are attractive for a preventive strategy.